PENGARUH INTENSITAS MENONTON YOUTUBE KIDS TERHADAP KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN - Nita, Siska Eka; Darmiyanti, Astuti; Rochimah, Nur (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The objectives of this study are to: 1) ascertain the level of YouTube Kids viewing in the Karawang Barat district; 2) ascertain the evolution of the speech abilities of children aged 5 to 6; and 3) ascertain the impact of YouTube Kids viewing intensity on the speaking abilities of children aged 5 to 6 in the Karawang Barat districts. Ex Post Facto was the qualitative method employed in the study, and 237 respondents were chosen by random sample procedures. We use an online tool to gather data. Analysis of research data: SPSS Version 23.0 for Windows is used in this study to do basic linear regression analysis. Based on the study's findings, it was determined that children in the Karawang Barat district watch YouTube Kids at a medium intensity, scoring a 57% presentation score, and that their speaking abilities develop at a preset rate of 59.9%, which is in line with expectations. A linear regression test yields a significance result (Sig) of 0.001<0.05, indicating a significant relationship (R square score of 4.2% ) between the amount of time children aged 5–6 watch YouTube Kids (X) and their capacity to speak.